Individual trauma : recovering from deep wounds and exploring the potential for renewal - Gow, Kathryn; Celinski, Marek J. (Psychology research progress series., 2012)
Life is a mix of good and bad happenings and sometimes terrible things happen to people. Trauma is evident across our lifespan; it is part of our lives. Trauma may not exert the same demands on the individual when they get on with their lives or experience other positive aspects of what life has to offer; however, it does not change its form from trauma to growth -- it stays there etched into our psyche as trauma. In simple terms, growth occurs alongside the traumatic etchings. This is a book that will provide some answers to psychologists, counsellors, social workers and mental health workers about what happens to people who are traumatised and how they 'get on with their lives'; it also gives some excellent examples of how therapies can assist them in moving forward in life's journey.